Insight into the 2004 Sumatra–Andaman earthquake from GPS measurements in southeast Asia - Vigny, C; Simons, W J F; Abu, S; Bamphenyu, Ronnachai; Satirapod, Chalemchorn; Choosakul, Nithiwatthn; Subarya, C; Socquet, A; Omar, Kamaludin; Abidin, H Z; Ambrosius, B. A. C. (Nature Publishing Group, 2005)
Data collected at ,60 Global Positioning System (GPS) sites in southeast Asia show the crustal deformation caused by the 26 December 2004 Sumatra–Andaman earthquake at an unprecedented large scale. Small but significant co-seismic jumps are clearly detected more than 3,000 km from the earthquake epicentre. The nearest sites, still more than 400 km away, show displacements of 10 cm or more. Here we show that the rupture plane for this earthquake must have been at least 1,000 km long and that non-homogeneous slip is required to fit the large displacement gradients revealed by the GPS measurements. Our kinematic analysis of the GPS recordings indicates that the centroid of released deformation islocated at least 200 km north of the seismological epicentre. It also provides evidence that the rupture propagated northward sufficiently fast for stations in northern Thailand to have reached their final positions less than 10 min after the earthquake, hence ruling out the hypothesis of a silent slow aseismic rupture.